Sleep, nutrition, and physical activity interventions to prevent obesity in infancy: follow-up of the Prevention of Overweight in Infancy (POI) randomized controlled trial at ages 3.5 and 5 y. Issue 2 (7th August 2018) - Taylor, Rachael W; Gray, Andrew R; Heath, Anne-Louise M; Galland, Barbara C; Lawrence, Julie; Sayers, Rachel; Healey, Dione; Tannock, Gerald W; Meredith-Jones, Kim A; Hanna, Maha; Hatch, Burt; Taylor, Barry J
ABSTRACT: Background: Our Prevention of Overweight in Infancy (POI) study suggested that a brief sleep intervention in infancy reduced the risk of obesity at age 2 y. In contrast, we observed no benefit from the nutrition and activity intervention. Objective: The objective of the study was to determine how these interventions influenced growth at ages 3.5 and 5 y compared with usual care (Control). Design: A follow-up of a parallel, 4-arm, single-blind, 2-y, randomized controlled trial in 802 women (86% European, 48% primiparous) recruited in pregnancy (58% response rate) was undertaken. All groups received standard Well-Child care with additional support for 3 intervention groups: FAB (promotion of breastfeeding, healthy eating, physical activity: 8 contacts, antenatal, 18 mo); Sleep (prevention of sleep problems: antenatal, 3 wk); Combination (both interventions). Follow-up measures were collected by staff blinded to group allocation. The primary outcome was child body mass index (BMI) z score, and secondary outcomes were prevalence of obesity (BMI ≥95th percentile), self-regulation (psychological measures), sleep, physical activity (accelerometry, questionnaires), and dietary intake (food-frequency questionnaire). Analyses were conducted through the use of multiple imputation. Results: Retention was 77% at age 3.5 y and 69% at age 5 y. Children in the FAB group had significantly higher BMI z scores than did Controls at age 5 y (adjusted difference: 0.25; 95% CI: 0.04, 0.47) but not at age 3.5 y (0.15; 95% CI: −0.04, 0.34). Children who received the Sleep intervention (Sleep and Combination groups) had significantly lower BMI z scores at age 3.5 y (−0.24; 95% CI: −0.38, −0.10) and at age 5 y (−0.23; 95% CI: −0.38, −0.07) than children who did not (Control and FAB groups). Conclusions: A conventional intervention had unexpected adverse long-term weight outcomes, whereas positive outcomes from a less conventional sleep intervention remained promising at age 5 y. More intensive or extended sleep intervention might have larger or longer-lasting effects and should be investigated. This trial was registered at clinicaltrials.gov as NCT00892983.